The Use of Local Mineral Formulas as a Feed Block Supplement for Beef Cattle Fed on Wild Forages - Khalil Khalil; M. N. Lestari; P. Sardilla; . Hermon (Media Peternakan, 2015)
The present research was carried out to study the diversity of mineral contents of wild forages and to evaluate the beneficial effect of mineral feed supplement formulated by using locally available materials on the performances of beef cattle. The present research was initiated by analyzing mineral contents of wild forages grown around Limau Manis campus areas. Forage samples were collected at 9 sampling areas scattered at plantation, conservation and idle lands. Samples were then analyzed for macro minerals of Ca, P, Mg, K, Na, and S and micro minerals of Co, Cu, Fe, Mn, Se, and Zn. Feeding trial was then conducted to evaluate the beneficial effect of supplementation of local mineral formulas (LMF) produced by using locally available materials on the performances of cattle. Feeding trial was conducted for 6 weeks by using 9 Simmentals cross bred heifers. The trial consisted of 3 treatments, i.e., P1: only grass without supplementation, P2: grass + LMF and P3: grass + mineral premix enriched LMF. Variables measured were: body weight, feed intake, FCR, feed cost and net return. Results showed that the highest macro mineral content of wild forages was Na of about 13.05±2.22 g/kg, varied from 4.1 to 23.8 g/kg, followed by K (11.09±1.43 g/kg) and Ca (6.10±1.09 g/kg DM). Three minerals of Mg, P, and S were found in relatively small concentrations of 1.34±0.30, 0.83±0.23, and 0.17±0.01 g/kg, respectively. Fe, Mn, Cu and Zn were found in relatively high concentrations. The highest concentration of micro minerals was Fe of about 613.8±128.9 mg/kg, followed by Mn of 143.9±23.3 mg/kg, while Zn and Cu were found in relatively small amount of about 31.3±5.5 and 13.2±2.5 mg/kg, respectively. Heifers supplemented with LMF (P2) and mineral premix enriched LMF (P3) showed higher body weight gain, lower FCR and net return than those cattle fed only grass (P1). The most profitable feeding strategy was by supplementation of heifers with mineral premix enriched LMF.Key words: wild forage quality, local mineral formula, ruminant mineral nutrition